PENGEMBANGAN PEMBELAJARAN BERBASIS WEB PADA MATERI TINGKAT BUNGA SEDERHANA DAN TINGKAT BUNGA MAJEMUK - Supriono K. Bulukaya; Yamin Ismail; Siti Zakiyah (Universitas Negeri Gorontalo, 2020)
This research aims to produce good mathematics learning media for Simple Interest Rate and Compound Interest Rates and find out the media's response and role towards students. This type of research is development research that begins with the development of web-based media. The development model used is a modified Four-D (4D) development model, namely the definition stage, the design stage, and the development stage. The research subjects were students of the Gorontalo State University mathematics study program. The results showed that the quality of the media based on the results of the validation by media experts was very valid. Students give a positive response. This shows that learning media can be used in the learning process, and learning media can increase student understanding.